ANALISIS SEMIOTIKA BATIK BONO SEBAGAI IKON DAERAH KABUPATEN PELALAWAN SEMIOTIC ANALYSIS OF BATIK BONO AS AN ICON OF THE PELALAWAN DISTRICT - Kiki Sefly Mulyanti; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Batik Bono is one of Riau batik produced at Andalan Batik House, which is the result of PT. Riau AndalanPulp and Paper. The name Batik Bono is taken from the tourist attraction of Pelalawan Regency, which is Bono's Wave and its motifs illustrate Pelalawan's characteristics. The motifs were taken from attractions to natural wealth owned, these motifs were patented at the Indonesian Ministry of Cooperatives and SMEs on March 19, 2015. Batik Bono has successfully attracted people's attention as evidenced by its sales turnover of 25 to 30 million per month. Batik Bono has also won awards from PT. RAPP, Ministry of Cooperatives and Department of Industry and Trade. This study aims to determine the meaning of denotation, connotation and myth in the five motifs of Batik Bono.This research uses qualitative research with Roland Barthes's semiology analysis approach. The subjects in this study are the five Batik Bono motifs that have patent rights. This research uses data collection techniques through documentation, observation, and literature study. To achieve data validity in this study, the authors used triangulation techniques.The results show the meaning of denotation contained in Batik Bono motifs describing the natural wealth of Pelalawan Regency, namely Bono Waves, Acacia Leaves, Eucalyptus Leaves, TimunSuri and Lakum. The meaning of the connotation obtained in this batik illustrates the character of the Malay community which has a spirit of courage, religious, social soul, harmony, openness, and humility. The meaning of the myth / ideology contained in Batik Bono is a myth about 7 ghosts because of its high shape, loud voice and being heard for many kilometers, Bono used to sink a lot of ships and eat victims causing fear in the midst of society, then myths about the character of the Malay community Brave, religious, and humble pelalawan. Keywords : Semiotics, Regional Icons, Pelalawan, Batik, Bono Wave